Implikasi Keputusan Presiden Nomor 12 Tahun 2020 terhadap Perjanjian Kerja dan Kontrak Bisnis di PT Bahana Mitra Pratama - Elza Qorina Pangestika; Arvita Hastarini; Kelik Endro Suryono; Said Munawar (Departement of Mathematics Education, 2021)
The decline in economic growth in Indonesia amidst the Covid-19 outbreak has resulted in a drop in income in various industrial, tourism and service sectors, resulting in layoffs. Apart from layoffs, the impact of Covid-19 also caused delays in several payment contracts, even ending in cancellation. Some of the contracts affected by Covid-19 are business contracts that are related to and depend on human movement, such as hospitality, transportation, tourism and manufacturing. Apart from that, there are also contracts in the financing sector such as leasing which are also affected by the downturn in the economy which results in delays in payments by debtors. One of the government's policies to save the national economy is by issuing a policy regarding the Designation of Non-Natural Disasters from the Spread of Covid-19 as National Disasters through Presidential Decree (Keppres) Number 12 of 2020.